New Zealand works for contrabassoon : [a thesis submitted to the New Zealand School of Music in partial fulfilment of the requirements for the degree of Master of Musical Arts in Performance] - Roud, Hayley Elizabeth (Massey University, 2010)
Abstract not available.
DVD of recital available with the hard copy
Keywords: Contrabassoon music; Contrabassoon and piano music; Composition (Music); Bassoon; New Zealand